Equality and freedom in South Africa: creating a democratic paradox? - Labuschagne, Pieter (University of the Free State, 2012)
South Africa’s democratic transformation from authoritarian rule to a constitutional democracy was a dramatic legal revolution that signalled the end of parliamentary sovereignty and its replacement by a supreme constitution. This adoption of a supreme constitution, including a bill of rights to protect individual rights, for the first time formally indicated the presence of a constitutional state in South Africa. The “legal revolution” had a direct influence on the way democracy would be defined and applied in the future. However, the emphasis in the Constitution on equality and freedom, in direct relation to democracy, may have created a potential paradox in the understanding and application of the concept in South Africa. This article investigates this potential paradox between equality and freedom in the application of democracy in South Africa

Suid-Afrika se demokratiese transformasie van ’n outoritêre regering na ’n konstitusionele demokrasie was ’n dramatiese staatsregtelike rewolusie wat ’n einde aan parlementêre soewereiniteit en die vervanging met ’n oppermagtige grondwet gemaak het. Die aanvaarding van ’n oppermagtige grondwet, met ’n handves van menseregte om individuele regte te beskerm, het vir die eerste keer in Suid-Afrika die teenwoordigheid van ’n konstitusionele staat bevestig. Hierdie “staatsregtelike rewolusie” het ’n direkte invloed op die wyse waarop demokrasie in die toekoms omskryf en toegepas sou word, uitgeoefen. Die klem wat egter in die grondwet op die waardes van gelykheid en vryheid in ’n demokrasie geplaas is, het egter ’n potensiële paradoks in die verstaan en toepassing van dié konsep geskep. Hierdie artikel ondersoek die potensiële paradoks tussen gelykheid en vryheid in die toepassing van demokrasie in Suid-Afrika.
Keywords: Constitution of the Republic of South Africa, 1996; Bill of Rights; Equality; Freedom